A REVEW : THERMODYNAMICAL STUDY OF FEW DOPED Ln (III)- QUINOLINE DERIVATIVES - Kailash Chand.,Niyaz mohammad; Jatolia S. N (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Spectral solutions and thermodynamical properties of a series of lanthanide (Ln(III))-quinoline derivatives were investigated. This study aims to elucidate the complex behavior of these doped compounds by examining their spectral characteristics and thermodynamic stability. The quinoline derivatives, known for their versatile coordination chemistry, were synthesized and doped with various lanthanides, including Eu(III), Tb(III), and Sm(III). Spectroscopic analyses, including UV-Vis, fluorescence, and NMR spectroscopy, revealed significant changes in electronic transitions and luminescent properties upon doping. Thermodynamic parameters such as enthalpy, entropy, and Gibbs free energy were determined using calorimetric techniques, providing insights into the stability and reactivity of these complexes. The doped quinoline derivatives exhibited enhanced thermal stability and unique electronic properties, attributed to the lanthanide’s influence on the quinoline backbone. The integration of spectral, thermodynamical studies presents a comprehensive understanding of Ln(III)-quinoline derivatives, highlighting their multifunctional applications in materials science and medicine. This work paves the way for future research into the development of advanced materials with tailored properties for specific industrial and biomedical applications.